Kinematic differences of elite and high-performance tennis players in the cross court and down the line forehand - Landlinger, J.; Lindinger, S. J.; Stöggl, T.; Wagner, H.; Müller, E. (Sports Biomechanics, 2010)
This study identified and compared the full body kinematics of different skill levels in the forehand groundstroke when balls were hit cross court and down the line. Forty-three three-dimensional retro-reflective marker trajectories of six elite and seven high-performance players were recorded using an eight-camera 400 Hz, Vicon motion analysis system. The six highest horizontal velocity forehands with reliable kinematics of all participants were analysed for each specific situation (a total of 156 analysed shots). Significant differences (p < 0.01) and large effect sizes were observed between elite and high-performance players in linear velocity of the shoulder (2.0 vs. 1.2 m/s), angular velocity of the pelvis (295 vs. 168 °/s), and angular velocity of the upper trunk (453 vs. 292 °/s) at impact. The elite group showed a tendency towards higher racquet velocities at impact (p < 0.05). No significant differences were found in angular displacement of the racquet, hip alignment, or shoulder alignment at the completion of the backswing; nor did angular displacement vary significantly at impact. Irrespective of the group, different shoulder, hip, and racquet angles were found at impact, depending on the situation. The results should assist coaches when striving to improve their players' forehand. Sprint start performance has previously been quantified using several different measures. This study aimed to identify whether different measures could influence the performance-based ranking within a group of 12 sprinters, and if so, to identify the most appropriate measure. None of the 10 performance measures ranked all sprinters in the same order; Spearman's rho correlations between different block phase measures ranged from 0.50 to 0.94, and between block phase measures and those obtained beyond block exit from 0.66 to 0.85. Based on the consideration of what each measure quantifies, normalised average horizontal external power was identified as the most appropriate, incorporating both block velocity and the time spent producing this velocity. The accuracy with which these data could be obtained in an externally valid field setting was assessed against force platform criterion data. For an athlete producing 678 ± 40 W of block power, a carefully set-up manual high-speed video analysis protocol produced systematic and random errors of +5 W and ± 24 W, respectively. Since the choice of performance measure could affect the conclusions drawn from a technique analysis, for example the success of an intervention, it is proposed that external power is used to quantify start performance.